No reduction in the cost of mating for Drosophila melanogaster females mating with spermless males. - Chapman, T.; Hutchings, J.; Partridge, L. (Proceedings. Biological sciences / The Royal Society., 1993)
Drosophila melanogaster females can incur a cost of mating, manifested as a decrease in longevity and lifetime reproductive success. We investigated whether the cost of mating was a cost of storing and/or receiving sperm by using two types of males that do not transfer sperm (transformer pseudomales and the male offspring of homozygous tudor mothers). Females that were intermittently exposed to males that did and did not transfer sperm did not differ in lifespan, in the absence of any differences in other costly aspects of reproduction, showing that there was no cost to receiving sperm. There was a cost of mating with spermless males; this suggested a potential cost of receiving accessory fluid. However, it was not possible to distinguish this possibility from other explanations, e.g. female injury at mating and the transfer of parasites. The reasons why females continuously exposed to males remated more than was in their reproductive interests is discussed.